In the footsteps of a quiet pioneer: Revisiting Pearl Jephcott’s work on youth leisure in Scotland and Hong Kong - Batchelor, Susan A. (Women's history review, 2018)
Pearl Jephcott’s (1967) research on Scottish teens, Time of One’s Own, is one of the first sociological studies of leisure in the postwar period. This research is remarkable not only for its emphasis on ‘ordinary’ young people but also for its ambitious and eclectic research design, which incorporates field research, sample surveys and task based participatory methods. The (Re)Imagining Youth team revisited Jephcott’s Scottish research alongside her survey of The Situation of Children and Youth in Hong Kong (1971) as part of a contemporary study of youth leisure and social change. This paper outlines our attempt to reimagine Jephcott’s work for the contemporary context, highlighting the ways in which her method was both a product of its time and ahead of its time